Synthesis of three dimensional controlled cable-stayed bridges subject to seismic loading. (1st January 2020) - Ferreira, Fernando; Simões, Luís
Highlights: An algorithm designs a controlled cable-stayed bridge subject to earthquakes. Three dimensional static and dynamic analysis and erection stages are considered. An analytic sensitivity analysis is provided for the controlled 3D bridge. Abstract: The use of dampers to mitigate the earthquakes effects on structures is an important area of research. In this work, an optimization algorithm is presented to solve the simultaneous structural-control design problem. The algorithm, sensitivity computations and three dimensional finite element models are developed in view of the specific design issues of this problem, in particular the static, dynamic and erection stage analysis. A non-linear elastic model includes the structural P-Δ effects and cable sag by using an equivalent Ernst modulus. A cable-stayed bridge with 350 m length is designed for the standard static and earthquake loading (according to the Eurocode regulation) using different tower-deck connections, in particular free (Case 1), fixed (Case 2) and with viscous dampers (Case 3). The results show that the optimum solutions have different geometries, cross sections and material distribution and that, in this example, the Case 3 solution is the most cost effective. The simultaneous structural-control optimization algorithm converges to a valid and cost effective solution in all cases.